NATURAL HISTORY OF ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION WITH TOTAL OCCLUSION OF INFARCT-RELATED ARTERY DURING SIX-MONTH FOLLOW-UP WITH OPTIMUM MEDICAL THERAPY - MANISH SAHA; SUBRATA BASU; AMRITA PAUL; KOUSTUV CHOWDHURY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives- Fate of STEMI patients on optimum medical therapy who remains asymptomatic following MI within 24 hours ,electrically and haemodynamically stable regarding their clinical status , LV function, with totally occluded infarct related artery. Methods-100 patients whose angiography performed 3 to 28 days after ST segment elevation myocardial infarction, showed total occlusion of the infarct-related artery with poor or absent ante grade flow,were put on optimum medical therapy in absence of contraindication and follwed up for 6 months. Results- At 1st month among 100 patients 46 ( 46% ) patients were asymptomatic.43 (43%)patients were presented with shortness of breath on exertion (SOBE) and rest 11(11%)had both chest pain and shortness of breath. In subsequent visit at 6 months 46 % patients were asymptomatic and rest presented with SOBE, none of them presented with significant chest pain Conclusion- In spite of optimum medical therapy patients with total occlusion of IRA and non viable myocardium developed progressive remodeling. Collateral flow is not adequate to prevent remodeling.Remodeling causes gradually progressive HF symptoms.If the patient has not developed new coronary lesion patients usually didn’t present with chest pain, shortness of breath was predominant symptoms in follow up in this group of patients.